Accelerating the oxidation of pork fat by illumination and fat oil for the production of Baijiu beverage. (27th August 2020) - Wei, Daiyue; Deng, Penghua; Tian, Xiaofei; He, Songgui; Li, Weigang; Wu, Zhenqiang
Abstract: BACKGROUND: Aged pork fat, deeply oxidized pork fat soaked in basic liquor for more than half a year, is an important material in producing Chi‐aroma Baijiu (CAB). With the expansion of production scale of CAB, innovative strategies for efficient production of aged pork fat are in great demand. The purpose of this study is to accelerate the lipid oxidation of pork fat and improve the productivity of aged pork fat. RESULTS: Results showed that polyunsaturated fatty acids (PUFAs) were the main reactant; generation reactions of lipid peroxides and free fatty acids (FFAs) were two limiting steps during the preparation of aged pork fat. Processing under illumination could alleviate the first limiting step by increasing the peroxide value and p ‐anisidine value of pork fat to 16.22‐ and 28.48‐fold higher than control samples and simultaneously the PUFAs were increased to 190.60 ± 0.19 g kg −1 . Soaking in basic liquor with deeply oxidized fat oil could alleviate the second limiting step by transferring FFAs from fat oil into pork fat. With more oxidized PUFAs, the acid value of the pork fat was 7.91‐fold higher than that of the control. CONCLUSION: Illumination and deeply oxidized fat oil could alleviate the two rate‐limiting steps of lipid oxidation and improve the productivity of aged pork fat significantly. The results are highly applicable in the CAB industry. © 2020 Society of Chemical Industry